Analisis SWOT dalam Penentuan Strategi Pelestarian Hotel Grand Inna Medan - Aura, Geby; Aulia, Cindy; Alfin, Muhammad; Rahim, Rizki; Nazira, Mawaddah; Syam, Fariz Harindra (Jurnal Teknik dan Teknologi Indonesia, 2024)
Grand Inna Medan Hotel is one of the oldest hotels in Medan City, originating from the Dutch colonial era as Hotel de Boer (1898) and later Hotel Inna Dharma Deli. As a heritage building, it faces both preservation challenges and strategic opportunities. This study aims to formulate a preservation strategy for Grand Inna Medan Hotel through a SWOT analysis, examining its historical and architectural values, existing physical condition, and internal and external factors. A qualitative descriptive method was used, based on field observation and documentation of the building's past and present condition, combined with an IFAS-EFAS weighting and rating matrix. The results show that the total internal factor score (Strength minus Weakness) is +0.500 and the external factor score (Opportunity minus Threat) is +0.500, positioning the hotel in Quadrant I of the SWOT diagram, which corresponds to an aggressive growth strategy. This indicates that Grand Inna Medan Hotel should leverage its Strengths, particularly its strategic location and heritage reputation, to capture tourism growth opportunities while continuing renovation and digital promotion efforts. The findings contribute to the discourse on adaptive heritage hotel preservation in urban Indonesia.